Reflecting and [Living]: Philosophy and Architecture of the Art and Performance of Talawang - Sihombing, Octa Maria; Mamarimbing, Natanael Yehezkiel; Ezra, Imanuel; Yardi, Apri; Anatasya, Chika Dwi; Kowy, Fifian Agustina; Munte, Alfonso (Eastasouth Institute, 2024)
This research examines Talawang shields, which have received little attention in scientific studies. Talawang shields are a cultural treasure for the Dayak people of Kalimantan, featuring intricate carvings, motifs, colours, and universes that blend art with local-global philosophical meanings. This is a qualitative research study that utilises previous studies as a secondary source of data. Additionally, the researchers provide evidence in the form of images of Talawang shields, which are considered an artistic luxury in Indonesia. The study also includes important interview results from credible sources with a cultural perspective to support the data. The results indicate that the Talawang shield serves as an art space for fashion and architecture, as well as a symbol of courage, responsibility, and loyalty. When presented to readers, observers, and art workers, the Talawang shield conveys multiple meanings.